System For Preparing Professors And Teachers For Pedagogical Management Of Students' Academic Activities In Higher Education Institutions (Eurasian Journal of Research, Development and Innovation, 2023)
In this article, the activities of pedagogical management of students' educational activities in the system of retraining and professional development of professors and teachers are studied.